2017
DOI: 10.1101/167015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using MinIONto characterize dog skin microbiota through full-length 16S rRNA gene sequencing approach

Abstract: The most common strategy to assess microbiota is sequencing specific hypervariable regions of 16S rRNA gene using 2 nd generation platforms (such as MiSeq or Ion Torrent PGM). Despite obtaining high-quality reads, many sequences fail to be classified at the genus or species levels due to their short length. This pitfall can be overcome sequencing the full-length 16S rRNA gene (1,500bp) by 3 rd generation sequencers.We aimed to assess the performance of nanopore sequencing using MinION™ on characterizing microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 63 publications
3
15
0
Order By: Relevance
“…Actinomyces odontolyticus and Rhodobacter sphaeroides seem to not amplify properly, neither with 16S rRNA gene or rrn operon. Previous studies also detected the same pattern for these specific bacteria even when using or comparing different primer sets [16, 21]. Overall, 16S rRNA primer set seemed less biased than rrn operon.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Actinomyces odontolyticus and Rhodobacter sphaeroides seem to not amplify properly, neither with 16S rRNA gene or rrn operon. Previous studies also detected the same pattern for these specific bacteria even when using or comparing different primer sets [16, 21]. Overall, 16S rRNA primer set seemed less biased than rrn operon.…”
Section: Discussionsupporting
confidence: 68%
“…Several studies targeting the full-length 16S rRNA gene have already been performed using nanopore sequencing to: i) characterize artificial and already characterized bacterial communities (mock community) [1517]; ii) characterize complex microbiota samples, from mouse gut [18], wastewater [19], microalgae [20] and dog skin [21]; and iii) characterize the pathogenic agent in a clinical sample [2224]. On the other hand, only two studies have been performed using the whole rrn operon to characterize mock communities [25] and complex natural communities [26].…”
Section: Introductionmentioning
confidence: 99%
“…The full protocol is available on protocols.io . (Cusco et al, 2017;Klindworth et al, 2013). First, we compared 3 fecal samples (run in duplicate) each from wild vs. captive animals of two primate species: the howler monkey (Alouatta seniculus) and the spider monkey (Ateles chamek).…”
Section: Case Studiesmentioning
confidence: 99%
“…Combined with the diverse kits offered, the ONT is a versatile alternative that can be used for multiple purposes in microbiome studies. There are some publications comparing Illumina and nanopore sequencing (Shin et al, 2016), although most of them focus on 16s rRNA gene sequencing (Cusco et al, 2017; Ma, Stachler, & Bibby, 2017). These previous studies showed a promising potential of nanopore sequencing for species detection with a high correlation between the results obtained by Illumina and ONT at the phylum and genus levels, despite the smaller basecalling accuracy from ONT compared with Illumina.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, analysis of the 16S rRNA gene is still preferred over shotgun metagenomics using the MinION and most of these studies have been conducted on mouse (Shin et al, 2016) and human gut microbiota (Leggett et al, 2017), proving consistent results for individual taxonomic profiles. Other animal microbiomes have also been sequenced with the MinION, the dog skin microbiota was characterized using a mock community and dog skin samples to test new 16s rRNA primers, finding accurate taxonomic results at the genus level (Cusco et al, 2017).…”
Section: Introductionmentioning
confidence: 99%